2015
DOI: 10.1111/tmi.12632
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hepatitis E virus infection during pregnancy in Benin

Abstract: Abstractobjectives Hepatitis E virus (HEV) is the cause of enterically transmitted non-A, non-C hepatitis (an infection that is particularly severe during pregnancy) in tropical and subtropical countries. As there are no published data concerning the prevalence of HEV antibodies in Benin, their presence was investigated in pregnant women undergoing routine HIV screening in a rural area in northern Benin and in pregnant women with acute non-A, non-C hepatitis. conclusions The circulation of HEV infection is sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
1
21
2
Order By: Relevance
“…Hepatitis E virus (HEV) infection is hyperendemic in many developing countries, especially in Southeast Asia and Africa, where there is poor sanitation and weak public-health infrastructures. 1,2 In developed countries, HEV infections occur through zoonotic transmission or contaminated blood products and can cause chronic hepatitis in immunocompromised individuals. 3 The HEV affects approximately 20 million persons annually worldwide, causing more than 56,000 deaths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis E virus (HEV) infection is hyperendemic in many developing countries, especially in Southeast Asia and Africa, where there is poor sanitation and weak public-health infrastructures. 1,2 In developed countries, HEV infections occur through zoonotic transmission or contaminated blood products and can cause chronic hepatitis in immunocompromised individuals. 3 The HEV affects approximately 20 million persons annually worldwide, causing more than 56,000 deaths.…”
mentioning
confidence: 99%
“…1,6 In humans, the infection is mainly transmitted by means of contaminated water, but also via food or blood transfusions, or vertically from mother to fetus. 2,6 Most HEV infections are self-limiting, but may develop into fulminant hepatitis with a case-fatality rate of 1-2% in the total population. In pregnant women, case-fatality rates of up to 40% were observed, especially during the third trimester of pregnancy.…”
mentioning
confidence: 99%
“…After screening by title and abstract, we selected 15 studies for the meta-analysis. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Articles were excluded on the basis of the following: review articles (n=251); book chapters (n=381); topics other than HEV infection in pregnant women such as HEV infection among blood donors, animal studies, duplicate, published before 2015, insufficient information (n=5193); and other languages (n=11) as described in Figure 2. The 15 studies reported on 8337 subjects, of which 1175 subjects were non-pregnant women and were subtracted from the total sample size.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…47 In Benin, a study conducted in 2011, 22.3% of total samples were HEV IgG positive, of which 45 (16.19%) were confirmed as positive by immunoblotting (if samples were positive, the test was repeated). 41 Among the three reported studies from China, an increase was observed a reported 11.07% seroprevalence of HEV IgG antibody in 2009-2010, 39 16.26% in 2011-2013, 38 and 21.78% in 2013-2014. 48 In Burkina Faso, a study conducted in 2014 reported that HEV IgG prevalence was 10.61%.…”
Section: Prevalence Of Hev Igg Antibody According To Regionmentioning
confidence: 93%
“…Furthermore, wide variations in reported seroprevalence of HEV antibodies in Africa during nonepidemic periods of acute and symptomatic hepatitis have been documented [33]. Additionally, studies have indicated that commercially Journal of Pathogens 3 available ELISA kits for anti-HEV antibodies differ dramatically in their sensitivity and specificity [34][35][36].…”
Section: Discussionmentioning
confidence: 99%